Aqueous enzymatic extraction and basic quality assessment of rice (Oryza sativa) bran oil - Hussain, Mohamed Reza (2011)
Rice bran, an industrial by-product of rice milling is rich in proteins, lipids, dietary fibers and antioxidant compounds, such as tocopherol, tocotrienol and oryzanol. This study evaluated the chemical composition of rice bran obtained from 4 Malaysian rice varieties. Results indicated that there is no significant (P>0.05) difference in chemical composition of all varieties alyzed. The effect of individual and mixtures of enzymes, namely cellulase (Celluclast 1.5L), protease (Alcalase), amylase (Termamyl), polygalacturonase (Viscozyme), and pectinase (Pectinex ULTRA SP-L) combined with other process parameters - dilution ratio, aqueous media, homogenization, mixing equipment, and centrifugation speed at different level on rice bran oil yield was evaluated. Results of the study showed that these enzymes had successfully extracted the rice bran oil from rice bran (75.66%) compared to that without enzymes (18.97%). Results also showed that using Alcalase resulted in higher oil yield compared to other enzymes. The maximum oil recovery of 70.3% was achieved at pH 9 and 70oC with <750 m particle size bran, 2.0% enzyme concentration and 3-hour extraction times. Iodine value (104.7± 0.3 g iodine/100 g oil), peroxide value (0.5± 0.2 meq/kg) and anisidine value (24.8± 0.2) of enzyme extracted oil obtained was comparable to that of commercially available rice bran oil. The oil however, was found to contain appreciable free fatty acid (2.6± 0.3 as % oleic acid), although still within the acceptable level for edible oils. It is encouraging to note that the enzyme extracted oil consisted of significantly higher concentration of both total and individual isomers (α-, β+γ, δ-) of tocopherol and tocotrienol compared SE oil. High level of oryzanol (2344 ppm) and carotenoids (-carotene and lycopene) (58.72 and 12.74 ug/100g) were also fond in the oil. The result showed that enzymatic extracted rice bran oil exhibited appreciable antioxidative activity that was significantly (P<0.05)highest compared to that of solvent extracted as measured by DPPH radical scavenging method, ferric thiocyanate (FTC) and thiobarbituric acid (TBA) tests. The study revealed that RB from Malaysian rice consisted of excellent level of nutrient especially many health promoting constituents and which could be considered as the most valuable rice milling process. The study also demonstrated that extracts of the RBO are a viable source of natural antioxidants or as value–added products in the preparation of specialty oil and for enrichment of certain products such as salad oil or functional ingredient in the development of functional food.